Law and discipline: A psychological trap? - Mazloum, Alaa (AUC Knowledge Fountain, 2017)
Over the past few centuries people have been trained to be subjects to state power. Today, one cannot define his existence without referring to one‟s relation as to the state. One defines him/herself as a subject to the power of state x or a term now used “citizen of state x”. This is a trap that state power have deliberately trained its citizens to believe to be their reality. For the past two centuries models of discipline and order have been constructed in Egypt. This thesis explores different disciplinary institutions, with a special focus on prisons, used by the state to discipline and order the Egyptian society. This thesis presents two faces of the disciplinary continuum. Starting with the first face, the paper explores and argues that the first use of disciplinary institution was particularly important in the early 1800s to create economically productive members of society. What disciplinary institutions tend to do is to control the psyche of the individual and create a certain perception of who this individual is and what he can do. The paper argues that incarceration results in continuous and systemic destruction of the psyche. In this way, it produces ill-suited individuals for life after prison due to prison‟s reinforcement of institutionally dependent behavior. In short, disciplinary institutions create dependency. The other side of the state disciplinary continuum is counter disciplinary represented by individuals who resist this power imbalance. Although the change brought forth is temporary, such acts of resistance have indeed succeeded in restructuring the balance of power. This paper encompasses many of the documented experiences of prisoners as evidence of the Foucault‟s theory on discipline presented. To do so, the paper heavily depends on works of literature and art, namely an Egyptian television production titled Segn il-Nesa (Women‟s Prison), which helps to humanize the law and procedures that govern the prison sector in Egypt. The paper builds the argument through drawing connections between theory and contemporary-and-historic examples on modes of discipline and disciplinary institutions.